Long-chain polyunsaturated fatty acid synthesis in fish: Comparative analysis of Atlantic salmon (Salmo salar L.) and Atlantic cod (Gadus morhua L.) Delta 6 fatty acyl desaturase gene promoters - Zheng, Xiaozhong; Leaver, Michael; Tocher, Douglas R (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2009)
Fish vary in ability to biosynthesise n-3 long-chain polyunsaturated fatty acids (LC-PUFA), with marine fish such as cod being inefficient in comparison to freshwater and salmonid fish. We investigated differences in the gene promoters of Δ6 fatty acyl desaturase (Δ6 FAD), a critical enzyme in LC-PUFA biosynthesis, in cod and salmon. Progressive deletions and targeted mutations of the promoters were tested for activity in a transfected fish cell line under low or high LC-PUFA treatment, and regions sufficient to direct transcription were identified. Comparison of these regions with sequences of corresponding regions of Δ6 FAD genes from mammals, amphibians and fish indicated a remarkable conservation of binding sites for SREBPs and NF-Y. In addition to these sites, a site was identified in salmon with similarity to that recognised by Sp1 transcription factor, and which was required for full expression of the salmon Δ6 FAD gene. The cod promoter was less active and lacked the Sp1 site. Eicosapentaenoic acid suppressed LC-PUFA synthesis in AS cells and also suppressed activity of the salmon Δ6 FAD promoter although this activity was likely mediated through sites other than Sp1, possibly similar to those recognised by NF-Y and SREBP transcription factors.